From classroom to workforce: a discrete choice analysis of Iranian nursing students’ job preferences - Khalil Moradi; Khadijeh Khosravi; Amir Jalali; Satar Rezaei (BMC Medical Education)
Abstract Aims This study evaluates both financial and non-financial preferences of nursing students to choose a hospital for work in future. Background In Iran’s healthcare system, the persistent shortage and uneven distribution of nurses have been significant challenges. Addressing such issues requires attention to nurses’ preferences, which can be instrumental in designing effective interventions. Methods In this cross-sectional study, 500 nursing students from Kermanshah University of Medical Sciences (KUMS) were surveyed using a convenience sampling method to determine their preferences for selecting the type of hospital in which they wish to work in the future. The study was conducted during the second half of 2023 using a discrete choice experiment (DCE) approach. To identify the most influential components on future nurses’ preferences, conditional logistic regression analysis was employed. Results The study revealed that an ideal and preferred hospital for nursing students is one that offers a high monthly salary, is located close to their homes, provides Rasmi contracts, has adequate facilities and equipment, has a low workload, and requires less than three years for career advancement. Additionally, the results indicated that the highest willingness to pay (WTP) was associated with the type of employment in the hospital, with nursing students willing to reduce their monthly salary by 27,303,610 IRR to change their employment status from Gharardadi to Rasmi. Conclusions The study confirmed that both financial and non-financial factors significantly influence nursing students’ choices regarding their future workplace. This research can serve as a valuable reference for future studies in this area. The findings can significantly aid in designing and implementing effective interventions aimed at retaining nurses in hospitals and attracting and keeping nursing staff in underserved areas.